Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/mnras/stw2339
|View full text |Cite
|
Sign up to set email alerts
|

KMOS view of the Galactic Centre – II. Metallicity distribution of late-type stars

Abstract: Knowing the metallicity distribution of stars in the Galactic Centre has important implications for the formation history of the Milky Way nuclear star cluster. However, this distribution is not well known, and is currently based on a small sample of fewer than 100 stars. We obtained near-infrared K band spectra of more than 700 late-type stars in the central 4 pc 2 of the Milky Way nuclear star cluster with the integral-field spectrograph KMOS (VLT). We analyse the medium-resolution spectra using a full-spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
150
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(183 citation statements)
references
References 89 publications
(145 reference statements)
16
150
4
Order By: Relevance
“…However, few of the coolest observed S-stars can only be explained by super-solar metallicity isochrones. Previous studies have reported observing metal-rich stars in the GC (Cunha et al 2007;Do et al 2015;Feldmeier-Krause et al 2017;Rich et al 2017). Pfuhl et al (2011) and Nishiyama et al (2016) observed similar stars within the NSC and described them as possible outliers due to different extinction or high metallicity.…”
Section: From Deep Spectra To H-r Diagrammentioning
confidence: 99%
“…However, few of the coolest observed S-stars can only be explained by super-solar metallicity isochrones. Previous studies have reported observing metal-rich stars in the GC (Cunha et al 2007;Do et al 2015;Feldmeier-Krause et al 2017;Rich et al 2017). Pfuhl et al (2011) and Nishiyama et al (2016) observed similar stars within the NSC and described them as possible outliers due to different extinction or high metallicity.…”
Section: From Deep Spectra To H-r Diagrammentioning
confidence: 99%
“…Thus, we work under the assumption that a large fraction of the Milky Way mass inside ∼ 100pc was brought in by infalling globular clusters (Antonini et al 2012). While observations show that in-situ star formation also contributed to the build up of the stellar populations inside ∼ 1pc (e.g., Feldmeier-Krause et al 2017), the relative contribution of the two formation channels (in-situ vs cluster inspirals) remains an open question. Moreover, we assume that the initial density distribution of clusters is proportional to the density distribution of field stars formed at the same epoch.…”
Section: Globular Cluster Formation and Evolutionmentioning
confidence: 99%
“…Our peak metallicity value at the GC is consistent with that from the GC field of APOGEE . A large fraction of super-solar stars has been found by Feldmeier-Krause et al (2017) based on low-resolution spectra in the nuclear star cluster. We will discuss in a forthcoming paper the chemical similarities as well as differences between the nuclear star cluster, the Galactic Center field population and the inner Galactic bulge.…”
Section: Mdfmentioning
confidence: 99%